Dental caries of lifetime residents in Baixo Guandu, Brazil, fluoridated since 1953: a brief communication - Saliba, Nemre Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Casotti, Cezar A. [UNESP]; Pagliari, Ana V. [UNESP] (Wiley-Blackwell, 2008)
Objectives: This study aimed to verify the dental caries prevalence in Baixo Guandu, the first Brazilian city to fluoridate its public water supplies; to compare the findings with the data from the national survey; and also to compare the prevalence in the 12-year-old age group with the data obtained before the beginning of the fluoridation. Methods: All the lifetime residents aged 5, 12, 15 to 19, and 35 to 44 years old were clinically examined (World Health Organization). Results: The means of dmft/DMFT were lower than in the Brazilian population living in fluoridated communities. The DMFT Index in 12-year-old residents decreased between 1953 and 2005 from 8.61 to 1.55. Conclusions: The addition of fluoride to public water supplies was an important ally in the improvement of the oral health of Baixo Guandu inhabitants.
Keywords: fluoride; water fluoridation; oral health; dental caries; dental public health